Adherence to Guideline‐Recommended Therapy—Including Supervised Exercise Therapy Referral—Across Peripheral Artery Disease Specialty Clinics: Insights From the International PORTRAIT Registry. Issue 3 (4th February 2020) - Saxon, John T.; Safley, David M.; Mena‐Hurtado, Carlos; Heyligers, Jan; Fitridge, Robert; Shishehbor, Mehdi; Spertus, John A.; Gosch, Kensey; Patel, Manesh R.; Smolderen, Kim G.
Abstract : Background: Underuse of guideline‐recommended therapy in peripheral artery disease (PAD) in administrative and procedural databases has been described, but reports on medically managed patients and referral to supervised exercise therapy (SET) in PAD are lacking. We aimed to document the use of PAD guideline‐recommended therapy, including SET in patients with PAD symptoms consulting a specialty clinic across 3 countries. Methods and Results: The 16‐center PORTRAIT (Patient‐Centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease: Investigating Trajectories) registry enrolled 1275 patients with new or an exacerbation of PAD symptoms (2011–2015). We prospectively documented antiplatelet medications, statins, smoking cessation counseling and/or therapy, and referral to SET: "2 quality measures" referred to the use of both statin and antiplatelet medications; "4 quality measures" to receiving all 4 measures. Median odds ratios were calculated to quantify treatment variation across sites. A total of 89% patients were on antiplatelets, 83% on statins, and 23% had been referred to SET. Of 455 current smokers, 342 (72%) patients received smoking cessation therapy/counseling. Overall, 77.2% of patients received "2 quality measures" and 19.7% "4 quality measures." The median odds ratio for 2 quality measures was 2.13 (95% CI, 1.61–3.56; P <0.001) and for 4 quality measures was 5.43 (95% CI, 2.84–17.91; P <0.001). Variability in adherence was not explained by country, except for referral to SET. The odds for SET referral in The Netherlands (70% referral rate) was nearly 100 times greater than in US sites (2% referral rate). Conclusions: Not all patients who have undergone a PAD workup at a specialty care facility are treated with evidence‐based care, especially so for SET.